Strategy Flexibility and Sustainable Digital Innovation - Rinto, Rinto Syahdan; Sirat, Abdul Hadi; Hadady, Hartaty; Jabid, Abdullah W. (International Journal of Business, Law, and Education, 2023)
This study aims to examine the effect of strategy flexibility on sustainable digital innovation. This research was conducted in Ternate City. The population in this study are all businesses in the city of Ternate. The sample in this study was determined based on a purposive sampling approach with total number of respondents of 115 people. Testing the hypothesis in this study using simple linear regression. The results of hypothesis testing indicate that the hypothesis in this study is supported. Next, recommendations for future research are discussed.